Comparing SARS-CoV-2 antigen-detection rapid diagnostic tests for COVID-19 self-testing/self-sampling with molecular and professional-use tests: a systematic review and meta-analysis - Katzenschlager, Stephan; Brümmer, Lukas E.; Schmitz, Stephani; Tolle, Hannah; Manten, Katharina; Gaeddert, Mary; Erdmann, Christian; Lindner, Andreas; Tobian, Frank; Grilli, Maurizio; Pollock, Nira R.; Macé, Aurélien; et al. (Scientific reports, 2023)
Self-testing is an effective tool to bridge the testing gap for several infectious diseases; however, its performance in detecting SARS-CoV-2 using antigen-detection rapid diagnostic tests (Ag-RDTs) has not been systematically reviewed. This study aimed to inform WHO guidelines by evaluating the accuracy of COVID-19 self-testing and self-sampling coupled with professional Ag-RDT conduct and interpretation. Articles on this topic were searched until November 7th, 2022. Concordance between self-testing/self-sampling and fully professional-use Ag-RDTs was assessed using Cohen’s kappa. Bivariate meta-analysis yielded pooled performance estimates. Quality and certainty of evidence were evaluated using QUADAS-2 and GRADE tools. Among 43 studies included, twelve reported on self-testing, and 31 assessed self-sampling only. Around 49.6% showed low risk of bias. Overall concordance with professional-use Ag-RDTs was high (kappa 0.91 [95% confidence interval (CI) 0.88-0.94]). Comparing self-testing/self-sampling to molecular testing, the pooled sensitivity and specificity were 70.5% (95% CI 64.3-76.0) and 99.4% (95% CI 99.1-99.6), respectively. Higher sensitivity (i.e., 93.6% [95% CI 90.4-96.8] for Ct < 25) was estimated in subgroups with higher viral loads using Ct values as a proxy. Despite high heterogeneity among studies, COVID-19 self-testing/self-sampling exhibits high concordance with professional-use Ag-RDTs. This suggests that self-testing/self-sampling can be offered as part of COVID-19 testing strategies.